Next-generation sequencing of mitochondrial DNA reveals pathogenic variants and protective haplogroup D4 in esophageal cancer - Jiang, Xiucheng; Shi, Lan; Zhao, Mei; Chen, Cui; Tang, Tao; Ji, Simeng; Lv, Bingbing; Jia, Lihua; Duan, Shuhan; Ma, Jinyue; Pang, Jiyu; Mu, Bo; et al. (Frontiers in Genetics, 2025)
IntroductionThe germline variations in the mitochondrial genome of esophageal cancer (EC) remain uncertain. Our study aimed to explore the distribution and pathogenicity of mitochondrial genome variations in EC, as well as to identify haplogroups associated with the development of EC.MethodsWe performed next-generation sequencing of the mitochondrial genomes from peripheral blood samples of 146 EC patients and 120 healthy controls. Variant annotation was performed using MitoMap, while pathogenicity prediction was conducted through tools such as MitoTip, SIFT, and PolyPhen2. Moreover, haplogroup classification was carried out using the Haplogrep3 platform.ResultsA total of 1299 mitochondrial variants were identified among 146 EC patients, including 171 novel (previously unreported) mutations. Compared with the healthy control group, the EC cohort exhibited a higher frequency of variants in genes such as ND2, COX1, COX2, 12S rRNA, and 16S rRNA. Three tRNA mutations (7496_T>C, 5771_A>G, and 5613_T>A) were predicted to be potentially pathogenic. Within the protein-coding regions, 14 variants were classified as deleterious based on predictions from 13 independent bioinformatic algorithms. Notably, mitochondrial haplogroup D4 was significantly associated with a decreased risk of developing EC. Furthermore, several mtDNA single-nucleotide polymorphisms (SNPs), including 302_A>AC, 1824_T>C, 1842_A>G, 3010_G>A, 8414_C>T, and 14668_C>T, showed significant associations with EC susceptibility.ConclusionWe found that the number of variations in multiple regions of the mitochondrial genome in the EC population was higher than that in the control group. Additionally, several potentially pathogenic variants were identified, and haplogroup D4 was suggested as a potentially protective haplogroup against the development of EC.